The intersection of entrepreneurship and selling: An interdisciplinary review, framework, and future research agenda - Matthews, Russell S.; Chalmers, Dominic M.; Fraser, Simon S. (Journal of Business Venturing, 2018)
Selling is integral to entrepreneurship, yet it has rarely been a focal topic of analysis for entrepreneurship scholars. To address this, we undertake a broad-ranging systematic literature review of research that in some way explores selling within entrepreneurial contexts. We inductively develop a framework that orders extant research into selling antecedents, activities, contexts, and outcomes. Then, drawing on these entrepreneurship-selling intersections, we suggest opportunity theory can be extended by integrating critical insights from selling literatures. In particular, we address ego-centric views of entrepreneurship which prioritize entrepreneurial agency, and advocate for the incorporation of customer agency into synchronized processes of opportunity identification, refinement, and exploitation. The article concludes that a promising avenue for future theory development resides in the study of situated sales interactions, which can serve as an empirical vista to the underexplored entrepreneur-customer nexus.